The Commoning of Public Goods by Residents of a Jakarta Apartment Complex. Issue 5 (20th October 2021) - Adianto, Joko; Gabe, Rossa Turpuk; Zamel, Muhammad Attariq
ABSTRACT: This study explores the commoning of public goods by residents of rental apartment buildings in Indonesia. Rental apartments have been Indonesia's means of providing affordable housing to people evicted from high-density kampung settlements. However, this mass-produced housing presents various socio-spatial problems for the underprivileged residents, who have responded in many cases by taking over and repurposing public areas. A rental apartment complex in Jatinegara, East Jakarta, was examined as a case study to understand the transformations of corridors on many of its floors. The study found that commoning among neighbours and building management transformed the public into common goods and that the occupants negotiated agreements among themselves to avert rivalry over the newly appropriated resources. This study recommends a new perspective of rental apartment design, regulations, and management to accommodate the commoning of the tenants to meet their unaccommodated needs.